Treating an Established Episode of Delirium in Palliative Care: Expert Opinion and Review of the Current Evidence Base With Recommendations for Future Development - Bush, Shirley H.; Kanji, Salmaan; Pereira, José L.; Davis, Daniel H.J.; Currow, David C.; Meagher, David J.; Rabheru, Kiran; Wright, David Kenneth; Bruera, Eduardo; Agar, Meera; Hartwick, Michael; Gagnon, Pierre R.; et al. (Journal of pain and symptom management, 2014)
Delirium is a highly prevalent complication in patients in palliative care settings, especially in the end-of-life context. To review the current evidence base for treating episodes of delirium in palliative care settings and propose a framework for future development. We combined multidisciplinary input from delirium researchers and other purposely selected stakeholders at an international delirium study planning meeting. This was supplemented by a literature search of multiple databases and relevant reference lists to identify studies regarding therapeutic interventions for delirium. The context of delirium management in palliative care is highly variable. The standard management of a delirium episode includes the investigation of precipitating and aggravating factors followed by symptomatic treatment with drug therapy. However, the intensity of this management depends on illness trajectory and goals of care in addition to the local availability of both investigative modalities and therapeutic interventions. Pharmacologically, haloperidol remains the practice standard by consensus for symptomatic control. Dosing schedules are derived from expert opinion and various clinical practice guidelines as evidence-based data from palliative care settings are limited. The commonly used pharmacologic interventions for delirium in this population warrant evaluation in clinical trials to examine dosing and titration regimens, different routes of administration, and safety and efficacy compared with placebo. Delirium treatment is multidimensional and includes the identification of precipitating and aggravating factors. For symptomatic management, haloperidol remains the practice standard. Further high-quality collaborative research investigating the appropriate treatment of this complex syndrome is needed.